2016
DOI: 10.1161/jaha.115.003144
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Event Prediction and Risk Reclassification by Coronary, Aortic, and Valvular Calcification in the Framingham Heart Study

Abstract: BackgroundWe determined whether vascular and valvular calcification predicted incident major coronary heart disease, cardiovascular disease (CVD), and all‐cause mortality independent of Framingham risk factors in the community‐based Framingham Heart Study.Methods and ResultsCoronary artery calcium (CAC), thoracic and abdominal aortic calcium, and mitral or aortic valve calcium were measured by cardiac computed tomography in participants free of CVD. Participants were followed for a median of 8 years. Multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
153
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 176 publications
(167 citation statements)
references
References 32 publications
9
153
1
4
Order By: Relevance
“…1721 Of interest, a recent report from the Framingham study showed that AAC, but not CAC, was significantly associated with total mortality. 28 …”
Section: Discussionmentioning
confidence: 99%
“…1721 Of interest, a recent report from the Framingham study showed that AAC, but not CAC, was significantly associated with total mortality. 28 …”
Section: Discussionmentioning
confidence: 99%
“…6 Epidemiologic studies demonstrated a graded increase in the risk of cardiovascular events across strata of CAC scores. 24 However, Agatston score does not account for CAC distribution and does not include information on the involvement of individual coronary arteries and on the involvement of proximal and distal segments. The results of studies using coronary CT angiography showed a strong association of coronary atherosclerosis burden, typically expressed as number of coronary arteries or segments with plaque, with adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The cardiovascular outcomes were defined in the Framingham Heart Study previously. 4,18 For the purpose of this study, major CHD events included recognized myocardial infarction and death from coronary heart disease. In the Framingham Heart Study, all study participants were under continuous surveillance for the development of outcomes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies in the Framingham Cohort have shown the presence of AAC, as seen on plain radiographs and MDCT scans, in middle-aged men and women, was associated with increased incidence of CVD, coronary heart disease (CHD), heart failure (HF), and cardiovascular and all-cause mortality. 22,23,24 Thus, the presence of extra-coronary calcium such as AAC could be an early marker of the likelihood of CAC progression and can further identify a subgroup of asymptomatic individuals who may be at increased risk of adverse CVD outcomes. Given the increased use of abdominal CT imaging in routine medical care, abdominal calcium is increasingly reported as an incidental finding and may have added clinical utility.…”
Section: Discussionmentioning
confidence: 99%